2008
DOI: 10.1677/joe-08-0406
|View full text |Cite
|
Sign up to set email alerts
|

Liver-derived IGF1 enhances the androgenic response in prostate

Abstract: Both IGF1 and androgens are major enhancers of prostate growth and are implicated in the development of prostate hyperplasia and cancer. The aim of the present study was to investigate whether liver-derived endocrine IGF1 modulates the androgenic response in prostate. Mice with adult, liverspecific inactivation of IGF1 (LI-IGF1 K/K mice) displayed an w80% reduction in serum IGF1 levels associated with decreased prostate weight compared with control mice (anterior prostate lobe K19%, P!0 . 05; dorsolateral pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
(62 reference statements)
2
10
0
Order By: Relevance
“…An in vitro study showed that IGF1 promotes growth of primary prostate cell cultures and human prostate cancer cell lines (De Nunzio et al 2012). In other studies, transgenic mice overexpressing human IGF1 in basal epithelial cells of the prostate were reported to develop prostate carcinoma at a high rate (DiGiovanni et al 2000), and mice with global or liver-specific inactivation of IGF1 were associated with reduced prostate size and androgen-dependent prostate growth (Svensson et al 2008). In addition, a meta-analysis of 42 observational studies demonstrated that elevated circulating IGF1 levels were significantly associated with prostate cancer risk (odds ratio, 1.21; 95% CI, 1.07-1.36) (Rowlands et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study showed that IGF1 promotes growth of primary prostate cell cultures and human prostate cancer cell lines (De Nunzio et al 2012). In other studies, transgenic mice overexpressing human IGF1 in basal epithelial cells of the prostate were reported to develop prostate carcinoma at a high rate (DiGiovanni et al 2000), and mice with global or liver-specific inactivation of IGF1 were associated with reduced prostate size and androgen-dependent prostate growth (Svensson et al 2008). In addition, a meta-analysis of 42 observational studies demonstrated that elevated circulating IGF1 levels were significantly associated with prostate cancer risk (odds ratio, 1.21; 95% CI, 1.07-1.36) (Rowlands et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In an LNCaP xenograft model, mice fed a high fat diet showed significantly increased serum insulin levels and experienced accelerated PCa growth compared to mice receiving a low fat diet, and serum from mice receiving the high fat diet was more mitogenic for LNCaP cells in vitro (Venkateswaran et al 2007). (DiGiovanni et al 2000), and mice with global or liver-specific inactivation of IGF1 show reduced prostate size and reduced androgen-dependent prostate growth (Svensson et al 2008). Indeed, a meta-analysis of 42 observational studies confirmed that raised circulating IGF1 levels were significantly associated with PCa risk (OR 1.21; 95% CI, 1.07-1.36), with weak evidence that this association was stronger for advanced PCa (Rowlands et al 2009).…”
Section: Insulin and Igf1mentioning
confidence: 98%
“…As in the prostate (38), IGF1 enhanced AR expression and was directly suppressed by miR-29a in mouse epididymis. Therefore, the suppression of miR-29a by AR might be mediated or at least partially mediated by IGF1.…”
Section: Discussionmentioning
confidence: 84%
“…A previous study revealed that the AR protein level is decreased in prostate from Igf1 knock-out mice (38). Therefore, we determined whether IGF1 can also activate AR expression in mouse epididymal cells.…”
Section: Mir-29a Represses Ar Expression Through Igf1 and P53mentioning
confidence: 89%